Подход к верификации правил с использованием лингвистических переменных в задачах интеллектуального анализа процессов - Чалый, Сергей Федорович; Кривчикова, А. А. (НТУ "ХПИ", 2013)
The approach to the rules verification in mining tasks processes aimed at identifying inconsistencies in the constraints on the process in terms of hidden (implicit) knowledge.
Keywords: бизнес-процессы; бизнес-правила; бизнес-процедуры; знания скрытые